2022
DOI: 10.3390/businesses2020010
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Music Content Marketing on User Satisfaction and Intention to Use in the Metaverse: A Focus on the SPICE Model

Abstract: The global market is experiencing stagnation and recession in the “untact era”, and the emergence of the metaverse provides platform support and presents a new paradigm. This study aims to provide a framework for content creators and marketers to verify the effectiveness of metaverse marketing. An analysis was carried out of the fit of the model and the hypotheses between the metaverse seamlessness, presence, interoperability, concurrence, and economic flow (SPICE) model factors, customer satisfaction, and pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Metaverse technology, which was originally used for games, is now actively used for different purposes in many areas such as meetings, incentives, conferences, exhibitions, schools, institutions, sports, entertainment, fashion, and retail, especially due to need (Hwang and Lee, 2022).…”
Section: Metaversementioning
confidence: 99%
See 2 more Smart Citations
“…Metaverse technology, which was originally used for games, is now actively used for different purposes in many areas such as meetings, incentives, conferences, exhibitions, schools, institutions, sports, entertainment, fashion, and retail, especially due to need (Hwang and Lee, 2022).…”
Section: Metaversementioning
confidence: 99%
“…Accordingly, the conceptual model of the factors affecting perceived usefulness is shown in Figure 7. Perceived trialability (Akour et al, 2022;Almarzouqi et al, 2022), perceived observability (Akour et al, 2022;Almarzouqi et al, 2022), perceived compatibility (Akour et al, 2022;Almarzouqi et al, 2022), perceived complexity (Akour et al, 2022), continuity (Hwang and Lee, 2022), spatial presence (Hwang and Lee, 2022), interoperability (Hwang and Lee, 2022), concurrence (Hwang and Lee, 2022) affect satisfaction. Therefore, the conceptual model of the factors affecting satisfaction is shown in Figure 8.…”
Section: Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dionisio (2013), for instance, when evaluating the progress in four distinct areas about Metaverse and the virtual world, reported that there are four factors for Metaverse, which is: immersive realism, ubiquity of access and identity, interoperability, and scalability [2]. In addition, RakGun Hwang (2022) developed a framework for content creators and marketers to question the efficacy of Metaverse marketing [3]. By using data from literature, Yuntao Wang and others (2022) analyzed the security and privacy threats and put forward the key challenges and countermeasures of the virtual world system [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, due to the recent proliferation of the contactless or "touchless" market due to COVID-19, the Metaverse has become more important than ever. To maximise marketing impact, establish a strategy that aligns with the context and format of your Metaverse platforms and content that can focus on promotion through normal exposure [15]. Depending on the adoption and popularity of the Metaverseand its development is still in its infancyas well as the BlueFocus layout, the Metaverse-related industries will assuredly occupy a certain advantage, hold the curiosity of users, carry out its new Metaverse marketing, implement a marketing upgrade and gain profits.…”
Section: Opportunitiesmentioning
confidence: 99%